Biodiversity offsets: towards an effective legal framework in South Africa - Midgley, Danjelle (Institute of Marine and Environmental Law, 2015)
South Africa is one of the most biologically diverse countries in the world. This biodiversity is under threat from economic, social and climate change pressures. One mechanism that could be added to South Africa's conservation tools, is that of the biodiversity offset where certain activities are designed to compensate for unavoidable harm to biodiversity resulting from development. The concept and theory of offsetting is controversial however, and not all commentators are in favour of encouraging a formal biodiversity offsetting regime in South Africa. This dissertation will explore the concept of biodiversity offsets in the regulatory permitting context and the controversies implicit in their theory and implementation. A framework for their inclusion in South Africa's environmental permitting context will be suggested.